2013
DOI: 10.1038/srep01401
|View full text |Cite
|
Sign up to set email alerts
|

An Aqueous Rechargeable Lithium Battery Using Coated Li Metal as Anode

Abstract: New energy industry including electric vehicles and large-scale energy storage in smart grids requires energy storage systems of good safety, high reliability, high energy density and low cost. Here a coated Li metal is used as anode for an aqueous rechargeable lithium battery (ARLB) combining LiMn2O4 as cathode and 0.5 mol l−1 Li2SO4 aqueous solution as electrolyte. Due to the “cross-over” effect of Li+ ions in the coating, this ARLB delivers an output voltage of about 4.0 V, a big breakthrough of the theoret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
139
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(147 citation statements)
references
References 29 publications
2
139
0
1
Order By: Relevance
“…Similar to the amorphous hollow carbon nanospheres, other amorphous carbon coatings can also lead to a superior cycling stability and high Coulombic efficiency 136. The virtue of the artificial interfacial protection can also be provided by graphene and hexagonal boron nitride hybrid,71 Li 3 N/PEDOT‐co‐PEG protecting layer,67, 137, 138 composite protective film,139 ceramic coating film,140, 141 LISICON layer142 ( Figure 12 ). …”
Section: Sei Regulationmentioning
confidence: 99%
“…Similar to the amorphous hollow carbon nanospheres, other amorphous carbon coatings can also lead to a superior cycling stability and high Coulombic efficiency 136. The virtue of the artificial interfacial protection can also be provided by graphene and hexagonal boron nitride hybrid,71 Li 3 N/PEDOT‐co‐PEG protecting layer,67, 137, 138 composite protective film,139 ceramic coating film,140, 141 LISICON layer142 ( Figure 12 ). …”
Section: Sei Regulationmentioning
confidence: 99%
“…The instability of perovskite-and NASICON-type solid electrolytes against metallic Li and the solid/liquid interface need to be improved as well. [257][258][259] It's reported that using polymeric solid electrolyte as a buffer layer could alleviate the instability of NASICON-type solid electrolytes, 64,243,[260][261][262] the long-term stability, however, needs further confirmation. 58 The development of solid electrolytes with superior conductivity and electrochemical stability will undoubtedly stimulate the development of Li-redox flow batteries together with a deep understanding of the fundamentals on ionic mobility in the bulk material.…”
Section: Polymeric Electrolytesmentioning
confidence: 99%
“…The average discharging voltage of aqueous Li-ion batteries with the LISICON film coated Li metal negatrode and a LiMn2O4 positrode can be up to 4.0 V, which leads to a specific energy value of 446 Wh kg ─1 . 24 The Mg metal was also considered to replace the Li metal in similar aqueous batteries. The Grignard reagent of PhMgBr was used to stabilise the Mg metal negatrode, whilst the positrode was still made of LiFePO4 to construct a novel Mg metal and Li-ion hybrid rechargeable aqueous battery.…”
Section: Aqueous Alkali Metal Ion Batteriesmentioning
confidence: 99%